Is there a circadian rhythm of postural control and perception of the vertical?. (25th November 2016) - Zouabi, A.; Quarck, G.; Martin, T.; Grespinet, M.; Gauthier, A.
ABSTRACT: Daytime activity is largely regulated by the day/night pattern. Various physiological and cognitive functions display a variation during the diurnal period, where individuals manage their balance, spatial orientation and consequently their perception of the vertical. However, findings concerning daytime changes of postural control quality remain contradictory, mainly due to methodogical considerations. The aim of our study is to evaluate the effect of time of day on postural control and perception of the vertical. Fifteen male subjects underwent six test sessions over a 24-hour period. Each session involved a postural balance test (static/dynamic; eyes open/closed) and a subjective evaluation of sleepiness, fatigue and subjective visual vertical (SVV) (light stick tilted from 10 to 40°; eight trials). No time-of-day effect was observed on postural balance. However, perception of the vertical fluctuates during the day and is better at 10 a.m. than at 10 p.m. Despite the gradual perception of the vertical deterioration over the day, postural balance does not show any fluctuation. This postural balance consistency throughout the day may be the result of compensation mechanisms.